Warunki funkcjonowania prawno-administracyjnej odmiany polszczyzny w XIX wieku = The situation of legal and administrative variety of Polish in the nineteenth century - Wojciechowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It has been suggested by historical linguists that the history of legal and administrative variety of Polish (the style of official documents) should be vividly examined. Therefore, this paper refers to this statement in many ways. First of all, the author of the paper emphasises that there has been very little research done on the description of the variety of Polish in question. Secondly, the conditions of functioning of legal and administrative variety of Polish during the partitions of Poland are briefly discussed.
Keywords: prawno-administracyjna odmiana polszczyzny; styl urzędowy; 19 w.; legal and administrative variety of Polish; official style; 19th century